2014
DOI: 10.5935/1678-9741.20140017
|View full text |Cite
|
Sign up to set email alerts
|

Managing the inflammatory response after cardiopulmonary bypass: review of the studies in animal models

Abstract: ObjectiveTo review studies performed in animal models that evaluated therapeutic interventions to inflammatory response and microcirculatory changes after cardiopulmonary bypass.MethodsIt was used the search strategy ("Cardiopulmonary Bypass" (MeSH)) and ("Microcirculation" (MeSH) or "Inflammation" (MeSH) or "Inflammation Mediators" (MeSH)). Repeated results, human studies, non-English language articles, reviews and studies without control were excluded.ResultsBlood filters, system miniaturization, specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
13
0
1
Order By: Relevance
“…effect, which has a short half-life (1.5 to 2 hours), not only on the postoperative inflammatory activity of serum hsCRP, TNF-alpha and VEGF, but also on TNF-alpha and VEGF in the carotid plaque. Previous publications have already demonstrated that glucocorticoids can interfere in the systemic inflammatory response, reducing concentrations of serum biomarkers and attenuating activation of the complement system and leukocyte and neutrophil adhesion, 13,14 but this effect has not been demonstrated with respect to hsCRP, TNF-alpha or VEGF, and the action of glucocorticoids on the behavior of biomarkers present in patients treated with EAC has not been assessed. After administering 30 mg/kg of intravenous methylprednisolone before surgery and before unclamping the thoracic aorta in 16 patients treated with revascularization of the myocardium, Kawamura et al 15 observed reductions in plasma concentrations of interleukins IL-6 and IL-8 at 1 hour, 2 hours and 3 hours after the aorta was unclamped.…”
Section: Discussionmentioning
confidence: 99%
“…effect, which has a short half-life (1.5 to 2 hours), not only on the postoperative inflammatory activity of serum hsCRP, TNF-alpha and VEGF, but also on TNF-alpha and VEGF in the carotid plaque. Previous publications have already demonstrated that glucocorticoids can interfere in the systemic inflammatory response, reducing concentrations of serum biomarkers and attenuating activation of the complement system and leukocyte and neutrophil adhesion, 13,14 but this effect has not been demonstrated with respect to hsCRP, TNF-alpha or VEGF, and the action of glucocorticoids on the behavior of biomarkers present in patients treated with EAC has not been assessed. After administering 30 mg/kg of intravenous methylprednisolone before surgery and before unclamping the thoracic aorta in 16 patients treated with revascularization of the myocardium, Kawamura et al 15 observed reductions in plasma concentrations of interleukins IL-6 and IL-8 at 1 hour, 2 hours and 3 hours after the aorta was unclamped.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the persistence of any degree of inflammation may be considered potentially harmful to the cardiovascular patient submitted to surgery [ 14 ] . Rubens & Messana [ 15 ] and Liguori et al [ 16 ] have concluded that the systemic inflammatory response is variable and is influenced by comorbidities exhibited by patients, non-pharmacological intervention during surgery, type of anesthesia, perioperative hemodynamic conditions, surgical aspects (surgical incision, duration, time of arterial crossclamping and need for blood transfusion) and postoperative evolution. In this study, we standardized general anesthesia and classical CEA with longitudinal arteriotomy, in order to keep our patients under the same perioperative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase-5 (PDE5) has the most desirable characteristics to be inhibited if secondary vascular and coagulation profile are to be preserved for a longer period. Therefore, if systemic actions are intended, as the needed in MOFS, it must be used a PDE5 inhibitor, that will maintain the NO-induced cGMP activation functioning for a long period, in the entire organic system [ 22 , 26 ] .…”
Section: Introductionmentioning
confidence: 99%